Masses in flight : the global crisis of internal displacement - Cohen, Roberta, 1940- (Book collections on Project MUSE., 1998)
"This book analyzes the causes and consequences of displacement, including its devastating impact both within and beyond the borders of affected countries. It sets forth strategies for preventing displacement, a special legal framework tailored to the needs of the displaced, more effective institutional arrangements at the national, regional, and international levels, and increased capacities to address the protection, human rights, and reintegration and development needs of the displaced."--Jacket